Organocatalytic synthesis of bio-based cyclic carbonates from CO2 and vegetable oils. Issue 66 (19th July 2015) - Alves, M.; Grignard, B.; Gennen, S.; Detrembleur, C.; Jerome, C.; Tassaing, T.
<x xml:space="preserve">Abstract</x> Optimal conditions deduced from in situ FTIR kinetic studies provide quantitative conversion of epoxidized linseed oil into carbonated linseed oil using a bi-component organocatalyst.